Development of vision system for humanoid robot - Li, Bingbing. (2011)
As the requirement of various functions of robot, vision system is a keen research area during the development of a humanoid robot and main constrain to the manipulation ability of the robot. During the operation of a humanoid robot, the basic function is to walking as a human, in which case, a good localization and obstacle avoidance system is required. An obstacle detection system was built for LOCH, using a stereo camera system which is the same its vision system. Two different project methods were involved in the project, i.e. an object to image method where images are project into an imagining plane for comparison and an image to object, where the images got from the cameras are directly project into the ground.